The Hadith on the Recommendation Not to Perform Excessive Prayer in Sunan Ibn Majah: A Study of Conflicting Hadiths - Ahmad Siddiq Setiawan; Muhammadiyah Amin; Muhammad Yahya (El-Sunnah)
This article examines the hadiths found in Sunan Ibn Majah regarding the recommendation to avoid excessive prayer and the hadith about prayer as the most virtuous deed, which appear contradictory, through the science of Mukhtalif al-Hadith. This study is qualitative research conducted through library research, gathering data from hadith collections and books relevant to the topic of discussion. The findings reveal that both the hadith recommending avoiding excessive prayer and the hadith on prayer as the most virtuous deed are authentic (sahih) and of the singular (ahad) type in terms of transmission. The study concludes that these two hadiths can be reconciled using the al-Jam‘u method through a contextual approach. Based on the compromise between these two hadiths, it is understood that the recommendation to avoid excessive prayer emphasizes that one should not overindulge in worship and instead prioritize simple but consistent acts of worship. On the other hand, the hadith about prayer as the most virtuous deed underscores the importance of not neglecting prayer, as it holds numerous virtues not found in other acts of worship or deeds. Thus, this hadith does not suggest continuous, uninterrupted worship but rather emphasizes the necessity of maintaining and not abandoning prayer.